Preliminary results on the plant regeneration from callus of Crinum latifolium L - Lien, Quach Thi; Thanh, Nguyen Duc (Academia Journal of Biology, 2015)
In this paper, preliminary results on the plant regeneration from callus of Crinum latifolium L. are presented. The calli were obtained from leaf and stem fragments of the mature trees. The calli were established on Mirashige and Skoog medium supplemented with auxin and cytokinin in different concentrations and combinations. A medium MSQ2 supplemented with 400 mg/l casein, 200 mg/l inositol, 1 mg/l kinetin was suitable for the induction and the growth of the calli derived from both leaf and stem. Plants were successfully regenerated from the callus grown on MSQ2 medium using a TSC1 medium supplemented with 6 mg/l kinetin, 0,2 mg/l NAA, 1 mg/l BAP.